REVIEWING PUBLIC HEALTH INTERVENTIONS ON REDUCING SEDENTARY BEHAVIOR IN WORKPLACES - Sri Indra Kurnia (Indonesian Journal of Multidisciplinary Science, 2022)
Changing behavior is a complex and major challenge. Thus, identifying effective public health interventions is important to do. This review has the main objective to identify and examine the most effective and appropriate practice to reduce sedentary behavior in the occupational environment. The main hypothesis of this review is “there is a significant reduction and interruption of sitting time among office-based workers after the implementation of the interventions”. Database searching was conducted in PubMed using the following search strategy: ("Sedentary Behavior"[MAJR]) AND ("office" [tiab] OR "workplace" [tiab])) AND ("adults" [tiab] OR "workers") AND ("intervention*" [tiab] or "program"). The search strategy resulted 124 relevant papers published within 2010-2021. Manual scanning and reviewing was done to deem eligibility of the studies as well as to eliminate irrelevant study design and topic. For example, studies which did not carry out public health intervention and studies only exploring the experiences of workers were excluded to the review group. The aim of this literature review is to critically evaluate the implemented public health interventions at reducing sedentary behavior among office-based workers. Overall, the findings from four different studies included in this review showed conflicting outcomes. This may be due to the nature of their approaches used during delivering the interventions (single-component intervention vs. multi-component strategies). howed that this strategy was unsuccessful and was not effective no changes in the primary outcome of the study (sedentary behavior was not reduced and physical activity was not increased). Thus, future intervention implementation will be more appropriate and friendly towards the general population.